Risk Factor Violations Associated With Sporadic Salmonella Cases - Appling, Xarviera S.; Lee, Petrona; Hedberg, Craig W. (Frontiers in Public Health, 2018)
FDA promotes assessment of routine restaurant inspection programs to measure trends in the occurrence of risk factors and compare data with national benchmarks. Reductions in the occurrence of risk factors should be accompanied by reductions in the occurrence of foodborne illnesses. The objectives of this study were to: (1) assess changes in risk factor violations in Bloomington restaurants between 2010 and 2015, in order to (2) compare patterns of risk factor violations in Bloomington restaurants that served sporadic Salmonella cases from 2010 to 2015 to these observed trends. FDA-based risk factor surveys were conducted in 2010 and 2015. Food contact surfaces were most frequently cited as out-of-compliance in both years. The proportion of inspections with employee health policy violations were reduced from 2010 to 2015, reflecting inspection priorities that were established after the 2010 survey. From 2010 to 2015, 154 sporadic Salmonella case exposures were reported from Bloomington restaurants. Food contact surfaces (odds ratio [OR] = 2.3; 95% confidence interval [CI] = 1.6, 3.5) and handwash facilities stocked (OR = 2.7; 95% CI = 1.7, 4.0) were more frequently found out-of-compliance in inspections that served sporadic Salmonella cases, in both individual year comparisons and in the overall comparison. The finding that violations such as food contact surfaces not being clean to sight and touch or sanitized before use and handwash facilities not being stocked with hand cleanser, sanitary towels, or hand drying devices, were more likely to be cited in sporadic Salmonella cases than during the FDA-based risk factor survey, suggests that these may contribute to an increased risk of Salmonella transmission in restaurants. Because restaurant inspections represent routine public health activities that are conducted by a broad range of agencies, establishing methods to analyze the results of these inspections across agencies and over time may help us better understand how risk factors cited on routine inspections can predict the likelihood a food establishment will be implicated in a foodborne illness case, in both sporadic cases and outbreaks.